Návrh komunikační strategie firmy - Duroňová, Petra (Vysoké učení technické v Brně. Fakulta podnikatelská, 2008)
Tato bakalářská práce se zabývá analýzou současného stavu firmy Renocar, a.s., jejího vnějšího a vnitřního okolí. Východiskem této práce jsou teoretické znalosti z oblasti marketingu, speciálně pak z oblasti komunikace. V praktické části jsou konkrétní analýzy aplikovány na firemní okolí, na základě zjištěných informací jsou navrženy změny, které by měly vést ke zlepšení a zkvalitnění firemní komunikace.

The bachelor work is focused on the analysis of up to date conditions of Renocar firm, its outside and inside invironment. The teoretical marketing knowledge, mainly from communication sphere are the aim of my bachelor work. The particular analysises are used for Renocar invironment in the practical part of the bachelor work, then the new changes are formed on the basis of discovered informations which should lead to improvement of the firm communication.
Proposal of a communication strategy for a business company
Keywords: Marketing; komunikace; strategie; propagace; sponzorství; Marketing; communications; strategy; promotion; sponzoring